New Ways of Improving Lives of People with Osteoporosis - Jankovic, Slavica; Babic, Jakov; Cojic, Marko (Recent Updates in Disease and Health Research Vol. 8, 2024)
In recent times, osteoporosis has taken epidemic proportions. It is a disorder that in time of industrialization and application of new technologies is starting to impact even the younger population. The use of modern devices in everyday life is resulting in a reduced level of human physical activity, consequently leading to an inactive way of life and an increase in number of people suffering from osteoporosis. According to the WHO definition, osteoporosis is a disease state characterized by loss of bone mineral density and bone loss which over time eventually results in fractures. As a disease, osteoporosis represents a great medical, social and economic challenge. Due to the recent years' increase in the number of people diagnosed with osteopenia and osteoporosis, there is a growing interest in this problem within the scientific community and among health professionals, and there has been a great number of attempts to develop guidelines for diagnosis, diagnostics and treatment for patients who are suffering from it. Going beyond its educational character, this dissertation also aims to point out potential positive aspects of Tae Bo exercises on people with osteoporosis and potential positive effects on bone mass, lowering of FRAX score and better quality of life. The study included 92 patients with osteoporosis diagnosis, who at the beginning and at the end of the study carried out laboratory blood, urine, and densitometry tests and filled out questionnaires of the ten-year risk of fracture (FRAX) and Quality Questionnaire QUALEFFO 31. The study was a prospective, randomized controlled study conducted on a group of women between 55 and 65. Research has shown that programs Tae Bo exercise can positively impact the greater bone mass and quality of life of people with osteoporosis. The study also points out that respondents tend to develop a positive attitude toward continuing physical activity once enrolled in a Tae Bo type of exercise. Accordingly, a working and a null hypothesis have been set. Research has shown that programs Tae Bo exercise can positively impact the greater bone mass and quality of life of people with osteoporosis. Considering the social and economic magnitude and the breadth of osteoporosis as a global and widespread problem, the main contribution of this study was to find new ways to mitigate its effects.